Declare yourself to be possessing a Criminal Act Because You Have Magical Powers as Meant in Article 252 of Law No. 1 of 2023 concerning Criminal Code - Purboyo, Ardi (PT. Riset Press International, 2023)
The meaning of the criminal policy of witchcraft is a formal offense. Witchcraft as a formal delict does not necessarily mean the death of someone who has been bewitched as a result, but the relationship between the witchcraft and the person who hired her. That relationship will be seen as a criminal act of conspiracy. Witchcraft offenses aim to prevent the emergence of new crimes in the form of fraud, extortion, or the emergence of victims as a result of people claiming to have supernatural powers. The delict of witchcraft is also intended to prevent the practice of taking the law into their own hands by members of the public against someone who claims to have supernatural powers and is capable of committing acts that can cause suffering to other people. Efforts to criminalize acts of witchcraft aim to increase the sense of security and justice for the community in relation to realizing the ideals of the nation as part of national development, so that it requires law enforcement and a legal culture. In this case, the role of legal experts and all law enforcers in providing legal protection to the community is important.